How Does the Introduction of Health Insurance Change the Equity of Health Care Provision in Bulgaria? - Markova, Nora. (Washington, D.C. : International Monetary Fund, 2006)
The study examines the effect of health care reform in Bulgaria in 1999 on the equity of health care financing. It explores the distribution of different types of health care financing by income. Furthermore, it separates the financial and social reasons for these differences, dividing them into economic and social inequalities. It suggests a method of distinguishing between financially based and "exclusion based" reasons for having progressive/regressive health care financing. Moreover, it looks at the social factors that shape health expenditure patterns and identifies those social characteristics that lead to exclusion from the health care system.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet